Enhancing Higher Order Thinking Skills through Utilization of Technology in Social Studies. - Hasni; Supriatna, Nana; Sapriya; Winarti, Murdiyah; Jumadi (SHS Web of Conferences, 2022)
This article departs from the author's analysis that, in building a new paradigm of Social Studies Education, learners as human beings are seen as subjects who think, act, are creative, constructive, and manipulative. The abilities that need to be developed in digital learning are: the ability to think related to cognitive aspects with a touch of technology. The purpose of this article is (1) to find out the strategies of social studies teachers in improving high level thinking skills (2) to study social studies material through the use of technology in improving the ability of students to think at a high level. The research method used is a qualitative method with a descriptive explanatory approach. Data collection was carried out through observation, interviews and literature reviews. The data analysis technique used is qualitative descriptive analysis with data collection, data presentation, data reduction and conclusions. The results of the study found that (1) Teachers are able to apply strategies to improve higher-order thinking skills in social studies learning with interpretation, analysis, evaluation and reference (2) Material that can be developed through the use of technology that is able to improve the ability to think at a high level in social studies learning is:Application of the problem solving model as innovative learning in Basic competencies (KD 3.4) with material Integrated pre-literacy life video viewing media and digital literacy.